Effects of oxidative stress on endothelial modulation of contractions in aorta from renal hypertensive rats - Seok Choi; Hye Rang Shin; Sang Hoon Kim; Mi Jung Lee; Jae Yeoul Jun; Hyun Lee Kim; Jong Hoon Chung; Cheol Ho Yeum (The Korean Society of Nephrology, 2014)
Background: Endothelial dysfunction is linked to exaggerated production of superoxide anions. This study was conducted to examine the effects of oxidative stress on endothelial modulation of contractions in chronic two-kidney, one-clip (2K1C) renal hypertensive rats. Methods: The 2K1C hypertension was induced by clipping the left renal artery; age-matched rats receiving sham treatment served as controls. Thoracic aortae were isolated and mounted in tissue baths for measurement of isometric tension. Results: Norepinephrine-induced contraction was augmented by the removal of the endothelium, which was more pronounced in sham rats than in 2K1C rats. Nω-nitro-L-arginine methyl ester, an inhibitor of nitric oxide production, had a similar augmenting effect. Vitamin C inhibited the contraction in aortic rings with intact endothelium from 2K1C rats but not from sham rats. The contraction was also suppressed by treatment with diphenyleneiodonium or apocynin, inhibitors of nicotinamide adenine dinucleotide/nicotinamide adenine dinucleotide phosphate (NADH/NADPH) oxidase, in the aortae with intact endothelium from 2K1C rats but not in those from sham rats. Superoxide anions generated by xanthine oxidase/hypoxanthine enhanced the contraction in the aortae with intact endothelium from sham rats, but had no effect in 2K1C rats. Enhanced contractile responses to norepinephrine by xanthine oxidase/hypoxanthine in sham rats were reversed by vitamin C. Conclusion: These results suggest that the effect on endothelial modulation of endothelium-derived nitric oxide is impaired in 2K1C hypertension. The impairment is, at least in part, related to increased production of superoxide anions by NADH/NADPH oxidase.